SUSTAINABLE COMMUNITY SERVICE INNOVATION: IMPLEMENTING SOLAR POWER AND WATER FILTERS ON POULTRY FARMS IN TULUNGAGUNG REGENCY - Asrori, Asrori; Nugroho, Pipit Wahyu; Yudiyanto, Eko; Witono, Kris; Adiwidodo, Satworo; Gunawan, Chandra; Rifa’i, Muhamad; Jaya, Harie Satiyadi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
A community service initiative was undertaken at UD. Risky Barokah, an egg-laying poultry farm in Sumberingin Kidul, Ngunut District, Tulungagung Regency. Operating since 2010 on a 7,000 m² site with nearly 10,000 chickens, the farm has faced persistent challenges related to water contamination and high electricity costs. To mitigate these constraints, a solar-powered water filtration system and a 1.1 kWp photovoltaic installation were implemented. The intervention was directed toward improving poultry health and egg productivity through access to clean water, reducing dependence on the electrical grid, and strengthening staff capacity through technical training. Outcomes demonstrated estimated monthly electricity savings of Rp247,500–Rp330,000 and consistent water quality that enhanced flock health and output, while simultaneously lowering the farm's carbon footprint. The project highlights the applicability of renewable energy and appropriate technology in promoting sustainable and cost-effective poultry production.